2023
DOI: 10.1073/pnas.2216722120
|View full text |Cite
|
Sign up to set email alerts
|

FDX1-dependent and independent mechanisms of elesclomol-mediated intracellular copper delivery

Abstract: Recent studies have uncovered the therapeutic potential of elesclomol (ES), a copper-ionophore, for copper deficiency disorders. However, we currently do not understand the mechanism by which copper brought into cells as ES–Cu(II) is released and delivered to cuproenzymes present in different subcellular compartments. Here, we have utilized a combination of genetic, biochemical, and cell-biological approaches to demonstrate that intracellular release of copper from ES occurs inside and outside of mitochondria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…127 Cuproptosis is primarily brought on by increased copper build-up and mitochondrial proteotoxic stress, which is mediated by Ferredoxin 1 (FDX1). 128 Elesclomol, an anticancer drug that targets mitochondrial metabolism, binds and transfers copper (Cu 2+ ) from the external environment to intracellular compartments. 129 Elesclomol is a powerful copper ionophore and stimulates copperdependent cell death.…”
Section: Cuproptosis Cell Death Pathwaysmentioning
confidence: 99%
“…127 Cuproptosis is primarily brought on by increased copper build-up and mitochondrial proteotoxic stress, which is mediated by Ferredoxin 1 (FDX1). 128 Elesclomol, an anticancer drug that targets mitochondrial metabolism, binds and transfers copper (Cu 2+ ) from the external environment to intracellular compartments. 129 Elesclomol is a powerful copper ionophore and stimulates copperdependent cell death.…”
Section: Cuproptosis Cell Death Pathwaysmentioning
confidence: 99%
“…FDX1 can rescue elesclomol‐induced copper‐dependent cell death 2 . In addition, elesclomol‐based copper transfer to non‐mitochondrial cuproproteins continues even in the context of FDX1 loss, demonstrating an alternative machinery of copper release 69 . The machinery of copper transport via elesclomol differs from other clinically utilized copper transport compounds.…”
Section: Cuproptosis a Unique Copper‐induced Cell Death Modality As A...mentioning
confidence: 99%
“…2 In addition, elesclomol-based copper transfer to non-mitochondrial cuproproteins continues even in the context of FDX1 loss, demonstrating an alternative machinery of copper release. 69 The machinery of copper transport via elesclomol differs from other clinically utilized copper transport compounds. In human cancer cells, FDX1 expression associates with prognosis, tumor immunity, and drug sensitivity, which is attenuated by elesclomol, without activation of caspases 3 and 7.…”
Section: Fdx1mentioning
confidence: 99%
“…The complex interplay of proteins coming together to form larger structuresknown as oligomerizationhas far-reaching effects on how cells function and maintain their stability. Research has consistently shown that proteins often act in their combined or “oligomeric” forms for key cellular processes, such as regulating genes and controlling enzyme activity. The behavior of these protein assemblies is not solely determined by their individual properties but is also shaped by the specific conditions within the cell. While in vitro studies provide immensely valuable information, they often fail to fully capture the true essence of protein behaviors in a cellular context. For example, they might miss the effects of changes in cellular components or neglect variables like protein concentration and post-translational modifications.…”
Section: Introductionmentioning
confidence: 99%